2014
DOI: 10.7874/kja.2014.18.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Reasons for Returning Hearing Aids

Abstract: Background and ObjectivesIncreases in older aged populations and exposure to complicated noise environments have increased the number of hearing-impaired patients, creating greater demands for hearing aids. We have assessed the reasons that individuals rejected wearing and returned properly prescribed hearing aids, as well as differences in individual factors between younger and elderly adults.Subjects and MethodsOf 1138 patients for whom hearing aids were prescribed at Kyung Hee University Medical Center Hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…These findings indicate a potential disparity in access to and utilization of hearing aids among different racial and ethnic groups. Regarding sex differences, it has been observed that a small percentage of patients, approximately 6%, return their hearing aids within the first three months of use, and this trend is more pronounced among women [ 27 ]. Regarding sex differences, the observation that a higher percentage of women return their hearing aids within the first three months of use suggests a potential disparity in their experience and satisfaction with the devices compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate a potential disparity in access to and utilization of hearing aids among different racial and ethnic groups. Regarding sex differences, it has been observed that a small percentage of patients, approximately 6%, return their hearing aids within the first three months of use, and this trend is more pronounced among women [ 27 ]. Regarding sex differences, the observation that a higher percentage of women return their hearing aids within the first three months of use suggests a potential disparity in their experience and satisfaction with the devices compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study on clinical reasons to return a HA depicted that inconvenient wearing of HA due to noise is the most frequent reason, while the cost is a major problem among younger adults. 19 Hartley and coauthors evaluated the reasons for not wearing HA among the Australian population. 20 These reasons were discomfort, does not help, cost, not working, and too noisy.…”
Section: Discussionmentioning
confidence: 99%
“…Third, a subgroup effect was found for participants with insufficient or good speech intelligibility in noise. This finding is interesting as people with moderate hearing loss (equivalent to the category insufficient hearing in the present study) seem to return their HAs more often than persons with severe hearing loss (Hong et al 2014). By improving HA outcomes with the DSL protocol, this high return rate could possibly be decreased.…”
Section: Control Groupmentioning
confidence: 90%